On the absolute continuity of measures corresponding to stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. Об абсолютной непрерывности мер, соответствующих случайным процессамB. Grigelionis. Apie matų, atitinkančių atsitiktiniems procesams, absoliutų tolydumą